Carte réduite du Golphe de St. Laurent contenant l'Isle de Terre-Neuve et partie de la Coste des Esquimaux, l'Isle Royale, l'Isle St. Jean et celle d'Anticosti & ca. - Bellin, Jacques Nicolas, 1703-1772 ([Paris, France], 1754)
Hand coloured. Prime meridians London, the Lizard (Cornwall), Tenerife, Ferro and Paris. Compass rose with rhumb lines. Decorative title cartouche. Relief shown by hachures and pictorially. Depths shown by soundings. Bar scale in English and French marine leagues. Includes time zones based on Paris. Shows anchorages and underwater features.